(untitled) (FULafia Journal of Science and Technology, 2021)
Misuse of prescription drugs and substances such as analgesics, opioids, depressants, hallucinogens, or stimulants is on the increase and a major concern for parents and the society due to its consequences on moral decay, crime, insecurity and health challenges. This study was aimed at determining the role of phenylthiocarbamide (PTC) taste sensitivity as a potential genetic marker for prescription drugs and substance misuse. Two hundred and thirty-two undergraduate students of the Nasarawa State University Keffi comprising of 133 males and 99 females were randomly selected and a structured questionnaire administered for the study. Stock solution of PTC prepared into various concentrations (0.005, 0.05, 0.25, 0.50 and 1.0) was used to determine the status of individual phenotypes.